Journey of lignin from a roadblock to bridge for lignocellulose biorefineries: A comprehensive review - Sharma, Vishal; Tsai, Mei-Ling; Nargotra, Parushi; Chen, Chiu-Wen; Sun, Pei-Pei; Singhania, Reeta Rani; Patel, Anil Kumar; Dong, Cheng-Di (The Science of the total environment, 2023)
The grave concerns arisen as a result of environmental pollution and diminishing fossil fuel reserves in the 21st century have shifted the focus on the use of sustainable and environment friendly alternative resources. Lignocellulosic biomass constituted by cellulose, hemicellulose and lignin is an abundantly available natural bioresource. Lignin, a natural biopolymer has over the years gained much importance as a high value material with commercial importance. The present review provides an in-depth knowledge on the journey of lignin from being considered a roadblock to a bridge connecting diverse industries with widescale applications. The successful valorization of lignin for the production of bio-based platform chemicals and fuels has been the subject of intensive investigation. A deeper understanding of lignin characteristics and factors governing the biomass conversion into valuable products can support improved biomass consumption. The components of lignocellulosic biomass might be totally transformed into a variety of value-added products with the improvements in bioprocess techniques that valorize lignin. In this review, the recent advances in the lignin extraction and depolymerization methods that may help in achieving the cost-economics of the bioprocess are summarized and compared. The industrial potential of lignin-derived products such as aromatics, biopolymers, biofuels and agrochemicals are also outlined. Additionally, assessment of the recent research trends in lignin valorization into value-added chemicals has been done and present scenario of technological-industrial applications of lignin with economic perspectives is highlighted. [Display omitted] •Lignin is a renewable and vital feedstock for the rapidly growing lignocellulosic biorefineries.•Revolution in lignin extraction and depolymerization methods is fate-determining.•The developments in analytical technology are a key towards lignin valorization.•Cutting-edge eco-friendly bioproducts can be produced through lignin valorization.